The language of emotion in the nineties poetic text - Ahmed Abidl Kareem Yassen Al Azawi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The study of language itself is a means of communication between the poet and the reader. It aims to show the creative aspect of the text through several functions, the most important of which is the subject of current study (the emotional function), the essence and purpose of which is the existence of an stimulus to issue a decision after the mind realizes that incentive. The poem, with its content, appears in an artistic form that the poet expresses in an unusual language. Its goal is to violate the usual system because the poetic image is nothing but an expression of a psychological and emotional state that the poet suffers as a result of a daily life situation. Any image within a work of art carries a feeling and performs the same function as the other partial image. The sum of these images constitutes the overall image that the poem ends with. From this principle, the subject of research began in clarifying the emotionalism of the nineties poet. So that the researcher can know the nature of his poetic language and translate it through poetic texts in which there was a lot of emotion and in which there was no calmness and satisfaction with everything that was available.